The Influence of Service Quality and Infrastructure for Visitor Interest in Cemara Island Tourism, Brebes - Dumadi, Dumadi; Wulandari, Hilda Kumala; Syaifulloh, Muhammad (Budapest International Research and Critics University, 2021)
The tourism sector has now become an important aspect of the economic progress of a country and is the main choice in regional development. The development of an area can open new tourist attractions for tourists that it is necessary to apply the right marketing strategy to bring in tourists and make tourists who have visited have an interest in visiting again, including the quality of services and tourism infrastructure. The purpose of the study was to determine and analyze the effect of 1) service quality on visitor interest, 2) infrastructure and infrastructure on visitor interest, and 3) service quality and infrastructure on visitor interest in Cemara Island Tourism, Brebes. The research population refers to the average number of visitors per month in 2020 which amounted to 3,248 visitors. Sampling using the Slovin formula with techniques incidental was 97 people. The data used primary data from the answers to the questionnaire. Hypothesis testing using SPSS 20. The theoretical basis used is the definition of tourism, service quality, infrastructure, and visitor interest. The results showed: 1) service quality partially had a significant effect on visitor interest, 2) infrastructure partially had a significant effect on visitor interest, and 3) service quality and infrastructure simultaneously affected visitor interest.